Lost back to the island : the complete critical companion to the classic TV series - St. James, Emily; Murray, Noel (Abrams Press, 2024)
"A comprehensive critical companion to the blockbuster TV show LOST, revisiting its core themes, lore, and impact on culture. For fans of one of the most successful and highly discussed shows in recent memory, LOST: Back to the Island is both a delightful time capsule and a rousing work of entertainment criticism. Before it premiered in the fall of 2004, LOST looked doomed to be an expensive, disastrous plane crash of a TV show. Instead, LOST was a massive hit, debuting with the biggest audience for a new drama on ABC in over a decade, reaching heights of over 23 million viewers at its peak, and holding on to a hefty fan-base for its entire six-season run. The elements that made the series seem like a boondoggle proved, instead, to be a big part of its appeal. Audiences loved the exotic island setting, became invested in the morally compromised characters, and feverishly tried to unravel the show's many mysteries. In LOST: Back to the Island, TV critics and veteran LOST recappers Emily St. James and Noel Murray revisit what made the show such a success and an object of enduring cultural obsession, twenty years later. Through essays, episode summaries, and cultural analysis, they take us back to the island and examine LOST's lasting impact--and its complicated, sometimes controversial legacy--with a clear-eyed and lively investigation"--